Necrotising enterocolitis biomarkers: a systematic review - Faizan, Muhammad Ashhad; Khalid, Iffat; Yeo, Asten; Fadel, Magdalina Mazheda; Mcmahon, Alannah; Gavigan, Philip; O’Neill, Saffron; Isweisi, Eman; Semova, Gregana; Roche, Edna F.; Branagan, Aoife; Meehan, Judith; et al. (Frontiers in Pediatrics, 2026)
BackgroundNecrotising enterocolitis (NEC) is a severe acute inflammatory condition of the gastrointestinal tract that predominantly affects preterm neonates. The variable and often nonspecific clinical signs, followed by rapid progression into fulminant disease, and the lack of standardised definitions and biomarkers, make this condition notoriously difficult to diagnose. This systematic review aims to outline the inflammatory pathways involved in the pathogenesis of NEC and to identify potential biomarkers associated with the initial stages of disease progression.MethodsFollowing the PRISMA guidelines, we conducted an electronic search of the available literature using the PubMed, Embase, and Cochrane electronic databases with the following search terms (“necrotizing enterocolitis” OR “necrotising enterocolitis” OR “NEC”) AND (“biomarker*” OR “biological marker”). Studies reporting data on the diagnostic accuracy of biomarkers for NEC were included. Results were restricted to full-text articles in English, available up to November 2024. Risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool.ResultsA total of 211 studies were screened, yielding 79 studies for analysis. Most studies evaluated the ability of biomarkers to differentiate Bell's stage ≥II NEC from controls or Bell's stage II from stage III. For identifying Bell's stage ≥II, faecal calprotectin (97.14% sensitivity, 100% specificity) and serum calprotectin (100% sensitivity, 96.4% specificity), as well as a panel consisting of urine proteins including Cystatin C (CST3), Pigment Epithelium Derived Factor (PEDF), and Retinol Binding Protein 4 (RET4) (96% sensitivity, 90% specificity), and maternal human milk oligosaccharide disialyllacto-N-tetraose DSNLT (90% sensitivity and specificity) demonstrated high sensitivity and specificity when sampled prior to or around the initial diagnosis of NEC. Interleukin 33 (IL-33) exhibited high accuracy.Systematic Review RegistrationPROSPERO CRD42024307046.